Business model reinvention for enabling disruptive innovation - Habtay, Solomon Russom (My University, 2011)
Over the last two decades, extensive research has been undertaken to understand incumbent firms’ adaptation behavior to disruptive innovation, considering technological change as the most important focus of analysis. Recently, there is an emerging literature that views disruptive innovation as a business model problem in which a technological innovation is deployed. In this literature, disruptive innovation is understood to be primarily a function of conflict between an incumbent’s traditional and an entrant’s new business model. This raises two major questions. First, although the original theory of disruptive innovation evolved from technological studies, this theory persists to explain all types of disruptive innovation over time (Markides, 2006: 19). Furthermore, disruptive innovation has always been studied from an incumbent firm perspective. With the need to shift the research focus from a technology to a business model, we also need a new framework to understand disruptive innovation taking the business model as the unit of analysis taking both the entrant’s and incumbent’s perspectives. Building on business model innovation studies (Govindarajan and Gupta, 2001; Normann, 2001; Hamel, 2000) and the established technology based disruptive innovation theory (Christensen and Raynor, 2003; Christensen, 1997), this study offers a systematic business model framework to comprehend disruptive phenomenon from both an incumbent’s and an entrant’s perspectives. Second, disruptive innovation studies predominantly focus on high-tech industries. Increasingly many low-tech industries are being affected by disruptive non-technological market-driven business model innovations. Considering that disruptive innovation theory is principally iii technology based, a review of the literature suggests that we know little about the differences between high-tech and low-tech market-driven disruptive innovations in terms of their evolutions, competitive and disruptive effects. From the strategic management literature point of view, the contribution of this study becomes even more relevant when the two questions are examined across economic regions. Although there is ample evidence that shows disruptive innovations are not always restricted to developed economies, little is known about how incumbents in developing economies adapt their organizations to disruptive business model innovations. This study takes South Africa as a development economy case-study. The empirical setting of the current study includes four South African industries: the mobile and IT industry (high-tech), banking, insurance and airlines (lowtech) industries. In addressing the two key question of the study, the dissertation presents the empirical analysis at the first-order (firm-level study) and second-order (high-tech vs. low-etch study) levels. The first-order study argues that an innovation creates and grows a niche market through radical product design, different core competencies and/or a different revenue model long before it becomes disruptive innovation. It proposes a framework that attempts to model the evolution of this trajectory from an entrant’s perspective. From the entrant’s perspective, a potentially disruptive business model innovation is a process that evolves over time in successive adaptations to endogenous and exogenous innovation drivers that shape the evolution and path of the new business model. An innovation becomes disruptive only when the new business model fully or partially affects an incumbent’s established business model and market. iv Taking the viewpoint of an incumbent firm, the first-order study further offers a framework that seeks to provide a causality model to comprehend the root cause of disruptive innovation and its impact on the incumbent’s traditional business model. One of the major causes of disruptive innovation is the incumbent’s entrepreneurial dilemma. This means that an incumbent’s success or failure is partly contingent on the senior corporate management’s entrepreneurship readiness that is manifested in terms of taking risk initiative, willingness and ability to take appropriate strategic approaches to enable disruptive innovation. By articulating the causes of disruptive innovation, it suggests four key strategic approaches an incumbent should follow to enable disruptive innovation. While the study finds common patterns for the causes and approaches among incumbents across the four industries at a firm-level, some of the hypotheses of this study could not be proven at an aggregated system level. Disruptive innovation is a relative phenomenon: Some innovations that are disruptive to some firms or industries may not be disruptive to other firms or industries. Therefore, the study further re-examines the aggregated firm-level outcomes by disaggregating the data into dichotomous technology versus marketdriven disruptive innovations. By conducting a second-order analysis at the innovation category level, this study adds considerably to extant innovation literature by establishing that a lowtechnology market-driven disruptive business model innovation entails different business model evolutionary processes, different disruptive effects and different managerial implications compared to high-tech disruptive innovation.
Keywords: Innovation; Business models; Disruptive innovation; Technological change; Strategic management